KECERNAAN INVITRO TUMPI JAGUNG YANG DIFERMENTASI MENGGUNAKAN MA-11 DAN EM4 DENGAN PENAMBAHAN MOLASES DAN UREA - Sukaryani, Sri; Windyasmara, Ludfia; Sariri, Ahimsa Kandi; Purwati, Catur Suci; Husein, Muhammad (Universitas Islam Balitar, 2025)
Corn tumpi is a byproduct of corn milling and is abundant in Indonesia, accounting for 8–15% of the total weight of ground corn kernels. However, its use as animal feed is hampered by its high crude fiber content, which reduces digestibility. MA-11 and EM4 are types of inoculum containing microorganisms that can produce fiber-degrading enzymes. Therefore, they can be used as inoculum in the fermentation process to overcome this obstacle and hopefully improve nutrient digestibility. The purpose of this study was to determine the effect of fermentation using MA-11 and EM4 on the digestibility of dry matter and organic matter in corn tumpi. The design used was a one-way RAL with three treatments, each replicated eight times. The treatments were P0: corn tumps plus molasses and urea (control); P1: corn tumpi fermented using MA-11 with the addition of molasses and urea; P2: corn tumpi fermented using EM-4 with the addition of molasses and urea. The observed variables include KcBK and KcBO.The collected data were analyzed using ANOVA; if the ANOVA indicated a significant difference, the DMRT test was carried out. The results indicate that corn tumpi fermentation can increase the average dry matter digestibility (KcBK) and the average organic matter digestibility (KcBO). The average value of KcBK is as follows: P0: 65.97%, P1: 74.03%, and P2: 70.92%. while the average value of KCBO is 61.47%; P1: 70.31% and P2: 65.77%. This study concludes that fermentation using MA-11 or EM4 on corn tumpi can increase the values of KcBK and KcBO, and that the inoculum yielding the highest results in KcBK and KcBO is MA-11.